Book as an Artistic Artifact - N. S. Murashova (Библиосфера, 2023)
A book is not only a carrier of information, but also the way of its aesthetic visualization. This actualizes the problem of understanding a book as an artistic artifact. The study of the book in this context implies the identification of several aspects: the art of the book; the existence of the book as an exhibit of museum and exhibition art space; the use of the book as a compositional and meaningful element of works of fine art, as a component of library design, living and working spaces; alterbooking and architectural structures in the form of a book. The article is devoted to the art of the book and its exhibition in museum and exhibition space. Its goal is to systematize the factors and features that should be considered in the study of the art of book for the possibility of its holistic interpretation from an art criticism perspective. The article considers the role of decoration in creating visual and verbal unity. The functions of illustration depending on the cultural and historical context as well as a purpose of the book are determined. Attention is paid to such phenomena of book art as fore-edge painting, artist’s book and art albums. The existence of the book in museum and exhibition art space is also considered. There are two types of exhibitions: single-subject exhibitions devoted exclusively to books and exhibitions with other objects participating in the realization of the semantic concept of a cultural event.